2023
DOI: 10.1038/s41467-023-41080-5
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional specular optical rotation in the charge ordered state of Kagome metal CsV3Sb5

Camron Farhang,
Jingyuan Wang,
Brenden R. Ortiz
et al.

Abstract: Kagome metals AV3Sb5 (A = K, Cs, Rb) provide a rich platform for intertwined orders, where evidence for time-reversal symmetry breaking, likely due to the long-sought loop currents, has emerged in STM and muon spin relaxation experiments. An isotropic component in the spontaneous optical rotation has also been reported and was interpreted as the magneto-optic Kerr effect. Intriguingly, the observed rotations differ by five orders of magnitude between different wavelengths and samples, suggesting more intricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Our result provides evidence that the rotation symmetry breaking of the 2 a 0 × 2 a 0 CDW states is not a structural effect but derived from the electronic reconstruction. Very recently, a similar rotation symmetry breaking effect was also reported in AV 3 Sb 5 via the MOKE and magneto-transport measurements. …”
supporting
confidence: 71%
See 1 more Smart Citation
“…Our result provides evidence that the rotation symmetry breaking of the 2 a 0 × 2 a 0 CDW states is not a structural effect but derived from the electronic reconstruction. Very recently, a similar rotation symmetry breaking effect was also reported in AV 3 Sb 5 via the MOKE and magneto-transport measurements. …”
supporting
confidence: 71%
“…The Sb- p z orbital forms a quasi-2D electron pocket around the Γ point. Moreover, there is a vHs at the M point near the Fermi level derived from the V- d orbital that possesses a large DOS (marked by the red arrow), which is widely believed to be the main cause for the strongly electronic interaction and the formation of CDW states by promoting the Fermi surface instability. , , …”
mentioning
confidence: 99%
“…Taking CsV 3 Sb 5 (CVS) as an example, the two most visible phase transitions are the CDW transition 2 , 23 at around 90 K and the superconductivity transition 2 , 23 at around 2.5 K. Interestingly, an increasing number of experiments have suggested the presence of additional phase transitions between these two temperatures, with one potential transition at approximately 35 K. Muon spin-rotation (μSR) experiments showed a sudden increase in the relaxation rate below ~ 35 K 24 , 25 ; STM, nuclear magnetic resonance (NMR), and elastoresistance measurement (EM) have pointed to the formation of electronic nematic order below ~ 35 K 8 ; A second-harmonic generation (SHG) experiment found prominent chirality along the out-of-plane direction emerges below ~ 35 K 10 ; Meanwhile, another STM experiment 26 found that the unidirectional coherent quasiparticles appear below 30 K. These studies altogether presented a puzzling physical picture, that the hidden phase below ~ 35 K simultaneously breaks the rotational symmetry and time-reversal symmetry. Moreover, its mechanism become more confusing since different conclusions have been reported recently, that spontaneously time-reversal symmetry breaking either coincides with CDW 27 – 29 or does not occur at all 30 , 31 , and rotational symmetry breaking also occurs at higher temperatures 26 28 . With the limited number of experimental findings, much remains unknown about this hidden phase, including the exact mechanism that breaks time-reversal symmetry, the spatial symmetry of the order, and its magnetotransport characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The CDW holds a crucial signiőcance because below T CDW a plethora of novel and intriguing physical phenomena have been reported. These include switchable chiral transport [13,14], specular optical rotation [15], or the presence of a chiral ŕux phase [16][17][18] accompanied by loop currents. This unconventional nature is also manifested in the superconducting order observed below 2.5 K for CsV 3 Sb 5 [19], with reports, for instance, of unconventional superconductivity [20][21][22][23], multi-charge ŕux quantization [24], and chiral superconductivity [25].…”
mentioning
confidence: 99%
“…In fact, it is not clear whether this exotic phenomena is intrinsic to the material or whether it is imposed by external perturbations [9]. Doubts also persist on the conservation of time-reversal symmetry, with contradictory results from muon spin spectroscopy [16,38,39] and magneto-optical Kerr effect [15,30,40].…”
mentioning
confidence: 99%